Harry Collins, Gravity’s Ghost: Scientific Discovery in the Twenty-first Century - Benda, Libor (Teorie vědy / Theory of Science, 2012)
Recenze / Review: Harry COLLINS, Gravity’s Ghost: Scientific Discovery in the Twenty-first Century. Chicago and London: The University of Chicago Press 2011, 187 s.